The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physrevb.90.085147
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and detrapping inSrAl2O4:Eu,Dypersistent phosphors: Influence of excitation wavelength and temperature

Abstract: SrAl 2 O 4 :Eu,Dy is presumably the best known persistent luminescent phosphor. At room temperature, its green emission remains visible for hours after switching off the excitation. It is known that upon lowering the temperature of the phosphor a second photoluminescence emission band arises in the blue part of the visible spectrum, although its origin is still the subject of discussion. In this paper we thoroughly study the origin of both emission bands in SrAl 2 O 4 :Eu,Dy and we attribute this to europium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
98
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 55 publications
12
98
0
4
Order By: Relevance
“…Hölsä et al [6] proposed the possibility of anomalous low-temperature luminescence, but the reported experimental data and theoretical calculations allow to conclude that the emission comes indeed from two different sites [4,7]. Nakazawa et al [8] observed the thermal quenching of SrAl 2 O 4 :Eu 2+ (doped with 1 mol%) but at much lower temperatures (100 K less) than all other publications.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hölsä et al [6] proposed the possibility of anomalous low-temperature luminescence, but the reported experimental data and theoretical calculations allow to conclude that the emission comes indeed from two different sites [4,7]. Nakazawa et al [8] observed the thermal quenching of SrAl 2 O 4 :Eu 2+ (doped with 1 mol%) but at much lower temperatures (100 K less) than all other publications.…”
Section: Introductionmentioning
confidence: 92%
“…The band gap of SrAl 2 O 4 is 6.6 eV [12]. The positions of the ground states can be estimated by the Dorenbos model [13], as it was done in [7] or it can be measured [14]. The europium ions in the two sites can be excited with UV-light.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…TL was recorded in a homebuilt setup, details of which can be found in Botterman et al 26 Before each TL measurement, the sample was thermally cleaned by heating to 220…”
Section: Methodsmentioning
confidence: 99%
“…Some authors assigned the 445 and 520 nm emission bands to emission of the Eu 2+ ion located at two nonequivalent strontium sites in the SrAl 2 O 4 host. 53,61 However, the two strontium sites in the SrAl 2 O 4 are very similar and differ only by a slight distortion of their square planes. 51 The similar coordination for both sites is expected to give rise similar luminescence properties due to comparable crystal field strengths and centroid shifts.…”
mentioning
confidence: 99%